THE FACTOR OF SPIRITUAL WELL-BEING AS A KEY FACTOR IN ENSURING A HEALTHY LIFESTYLE - Asila Sadikova (Journals Park Publishing, 2025)
In the article has been analyzed the factor of spiritual well-being as a key factor in ensuring a healthy lifestyle by the helping scientific literature.
Keywords: Factor, spiritual well-being, key factor, society, healthy lifestyle.